Comparing umbilical cord arterial blood gas findings in pregnancies with and without gestational diabetes mellitus following elective cesarean section: a multicenter retrospective cohort study in Iran - Fatemeh Golshahi; Zufa Iqbal; Zahra Hamidi Madani; Zeynab Zamanpour; Behrokh Sahebdel; Nafiseh Saedi; Somayeh Khanjani; Jafar Golshahi; Mahboobeh Shirazi; Pegah Rashidian; Mohammadamin Parsaei (BMC Pregnancy and Childbirth)
Abstract Background Gestational diabetes mellitus (GDM) is linked to adverse fetal outcomes like macrosomia and neonatal hypoglycemia, with its global incidence increasing. While prior research indicates GDM may impair placental function and fetal oxygen delivery, direct evidence is limited. This study compares umbilical cord arterial blood gas measurements in pregnancies with and without GDM. Methods This retrospective study analyzed medical records from four hospitals in Tehran, Rasht, Ahvaz, and Isfahan in Iran, focusing on term singleton pregnancies (gestational age ≥ 37 weeks) that underwent elective cesarean sections between January and July 2024. Exclusions included maternal age < 18 or > 45 years, pre-existing diabetes, thyroid, hypertensive, malignant, metabolic, or autoimmune disorders, intrauterine growth restriction, hypertensive disorders of pregnancy, and substance use during pregnancy. GDM was diagnosed using a 75-gram oral glucose tolerance test at 24–28 weeks. Primary outcomes included umbilical cord arterial blood gas measures (potential of hydrogen [pH], partial pressure of carbon dioxide [PCO2], partial pressure of oxygen [PO2], bicarbonate [HCO3], and base deficit). The neonatal outcomes were measured as secondary outcomes. Statistical analyses utilized Chi-square, Fisher’s exact, and independent t-tests. Results Data from 430 pregnancies, including 87 with GDM, were analyzed. Pregnancies with GDM showed significantly lower pH (7.33 ± 0.08 vs. 7.36 ± 0.06, P-value = 0.006) and greater base deficit (-1.82 ± 3.79 vs. -0.50 ± 2.74 mEq/L, P-value = 0.003). However, no significant between-group differences were observed in PCO2, PO2, or HCO3 (P-value > 0.05). Furthermore, we observed no significant differences in the mean birthweight, 1-minute, or 5-minute Apgar scores (P-values > 0.05), while neonates in the GDM group required more resuscitation (28.7% vs. 12.0%, P-value < 0.001) and neonatal intensive care unit admissions (34.5% vs. 16.9%, P-value < 0.001). Conclusions Pregnancies with GDM showed higher umbilical cord blood acidity, indicating impaired placental function and reduced fetal oxygenation. These findings underscore the need for enhanced monitoring, such as regular fetal surveillance and close glycemic control, along with timely interventions like early neonatal resuscitation protocols and preparedness for neonatal intensive care unit admissions, to mitigate impaired fetal oxygenation in GDM. Trial registration Not applicable.